Sosialisasi Penguatan Integritas Mahasiswa dalam Mencegah Budaya Anti Korupsi di Lingkungan Universitas Lampung - Sari, Dian Permata; Saputri, Rima Yuni; Nurjanah, Siti (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS LAMPUNG, 2024)
Corruption is a serious challenge that harms the country financially and morally. The Pancasila and Citizenship Education (PPKn) Study Program at the University of Lampung initiated a program to strengthen the integrity of third-semester students to build an anti-corruption culture. This activity aims to increase students' understanding, awareness, and commitment to integrity values, such as honesty, responsibility, and transparency. The methods used include problem analysis, poster trials through focus group discussions (FGD), socialization, and evaluation. The results showed an increase in students' understanding of integrity. Posters as an educational medium have proven effective in conveying anti-corruption messages, while motivating students to apply these values. Students also showed a higher commitment as agents of social change in realizing cultural integrity on campus. However, challenges such as tolerance for dishonest behavior in the social environment still need to be overcome. Therefore, strengthening is needed through the integration of anti-corruption values ​​in the curriculum, public campaigns, and ongoing evaluation. This step is expected to be able to create a young generation with integrity who supports good governance and becomes a driving force for eradicating corruption.